Analysis Of Factors Affecting Corn Farmers 'Revenue In Gorontalo District - Wiwi Pratiwi; Syarwani Canon (Jambura Equilibrium Journal, 2019)
This study aims to determine what factors influence the income of corn farmers in Gorontalo district (case study of Poor Corn Farmers in Gorontalo District). The data in this study are primary data by distributing questionnaires to poor corn farmers in Gorontalo Regency. The data analysis technique in this research is multiple regression. The results of this study indicate that the factors that influence the income of poor corn farmers in Gorontalo District (1) simultaneously the area of farmer Education, number of dependents in the family, land ownership status and the use of technology in corn farming significantly influence the income of poor corn farmers) in Gorontalo Regency. (2) partially only land area and land ownership status have a significant effect on the income of poor corn farmers in Gorontalo Regency. Keywords: Income, Corn Farming, Poor Farmers